Exploratory marketing study on gender perceptions on services. - Thio, Yi Ling. (2008)
This paper studies how gender difference might affect consumer’s perception on service provided. Based on our findings, the retail managers of intellectual and technology products do not need to regard gender effect and train sales representatives based on higher sensitivity to the differing information needs of the customers.